Eco-friendly and agile energy strategies and policy development - Danish, Mir Sayed Shah 1987-; Senjyu, Tomonobu 1963- (IGI Global, 2022)
"This book covers the importance of the state-of-the-art findings of researchers in the field of eco-friendly energy agile strategy and policy development, following processes and their technologies exploitation on a broad theme of sustainable development"--
Includes bibliographical references and index. - Mode of access: World Wide Web
Keywords: Renewable energy sources; Sustainable development; Energy conservation -- Government policy; Energy policy